DISAGREEING STRATEGIES IN ENGLISH (Journal of Foreign Language Studies, 2024)
This paper discusses linguistic strategies for expressing disagreement in English. Twenty eight strategies were systemized and analyzed with illustrations based on the theoretical framework by Brown and Levinson (1987) and the findings in major studies on these linguistic behaviors. The system of strategies for expressing disagreement as a face threatening act (FTA) was describe in details, from not doing the act to doing the act. When performing FTA, the speaker (S) can choose a direct, softened or emphasized disagreement based on their purposes. However, it should be noted that the disagreeing strategies were presented in a practical rather than theoretical manner with the hope that they can be successfully applied to teaching, studying, and expressing disagreement in English.
Keywords: speaker (S); hearer (H); addressee (A); face threatening act (FTA)